The Phenomenon of Baris Pendet Dance at Dalem Tanjung Sari Temple, Tanjung Bungkak Traditional Village, Denpasar City, Bali - Sariada, I Ketut; Swarsana, I Putu; Sulistyani, Sulistyani; Yulianti, Ni Ketut Dewi; Santika, Sang Nyoman Gede Adhi (Institut Seni Indonesia Bali, 2025)
This research aims to obtain a holistic understanding of Baris Pendet Dance in Tanjung Sari Temple, Tanjung Bungkak Traditional Village, Denpasar City, Bali Province. This research was conducted by analyzing aspects of dance form, function, and philosophical meaning of Baris Pendet Dance. This research uses a qualitative research model with a descriptive approach. Data collection using observation techniques, interviews, literature studies and documentation studies. Several theories such as Aesthetic Theory, Structural Functionalism Theory, and Semiotics Theory are used to analyze data about the form, function and meaning of dance. The results showed that Baris Pendet dance in Pura Dalem Tanjung Sari is a group dance consisting of eight boys who have not yet entered puberty. The function of this Baris Pendet dance is the function of ritual, spectacle, and cultural preservation. Denotatively, this dance symbolizes respect for the value of spirituality in periodic rituals at Tanjung Sari Temple. While connotatively, this dance symbolizes the welcoming of humanity to the descent of the gods during the ceremony held at Tanjung Sari Temple.